A Race to the Top? Competitive Pressure and Magnet Adoption Among US Hospitals 1997–2012. Issue 4 (April 2017) - Richards, Michael R.; Lasater, Karen; McHugh, Matthew
Abstract : Background: Care quality continues to be a focal point within US health care. One quality innovation is the Magnet recognition program for hospitals, which is a nurse-driven initiative emphasizing care and patient-safety improvements. To date, Magnet hospitals have been associated with better outcomes, but their distribution is highly uneven. Relatedly, little research has characterized what factors drive Magnet adoption (eg, competitive pressure from other hospitals). Objective: To examine if hospitals respond to more competing hospitals becoming Magnets by also becoming Magnet institutions. Research Design: We use longitudinal data from the American Hospital Association, 1997–2012, and estimate hospital-level fixed-effect regressions to capture the association between Magnet adoption among competitors and a hospital's own likelihood of becoming a Magnet. We also explore heterogeneity in the relationships according to a hospital's standing within its market. Results: Having more competitors become Magnets strongly predicts that a given hospital seeks Magnet recognition; yet, a hospital's market position and prevailing competition levels are moderating influences. Conclusions: A large literature links Magnet hospitals with better outcomes for patients and nurses, and more recent evidence suggests a business case for becoming a Magnet. We find evidence that hospitals seem motivated by competitive pressure, which suggests economic considerations in the decision to invest in costly care improvements. Abstract : Supplemental Digital Content is available in the text.